Computerized Tomography Scans for Ankle Fracture: Diagnosis, Management and Surgical Plan Modifier. Issue 1 (January 2022) - Mansur, Nacime S.; Celestino, Fausto Santana; Neves, Caroline; Pereira, Vinícius F.; Vargas Silva, Pedro Debieux; Matsunaga, Fabio Teruo; Nery, Caio A.; Astur, Diego C.
Category: Trauma; Ankle Introduction/Purpose: Ankle fractures are one of the most operated injuries in orthopedic practice. The decision upon the best management is based on the displacement of the bone fragments and the presence of associated lesions (osseous and/or soft tissues). The therapeutic decision is classically established upon plain radiographs, which might be temerarious due to the usual difficulty in analyzing those exams. In recent years, some authors have advocated that computed tomography could be used as an assistant instrument on the decision-making. Our study aims to demonstrate the superiority of the association between both methods on diagnosis, therapeutic decision, and surgical plan for these injuries. Methods: Patients diagnosed with an ankle fracture, between 2011 and 2016, and assessed with CT and X-ray were included in our investigation. Seven examiners with different degrees of experience analyzed the exams, determined the injuries, chose how they would treat, and the defined surgical strategy when applicable. This was done, at first, only with radiographs and after with the combination of CT and radiographs. The data were statistically compared. Results: Fifty-three patients were included. The medial malleolus fractures characteristics (posteromedial fragment and anterior colliculus), the presence of posterior malleolus fracture and its characteristics (displacement, bone fragment greater than 25%, posteromedial or posterolateral segment), syndesmosis injury, and the absence of deltoid ligament lesion were more noticeable from the combination of CT and radiography. Concerning surgical treatment, the prone position, the posterolateral surgical approach (rather than anterolateral) on lateral malleolus osteosynthesis, the decision to surgically treat the posterior malleolus fracture (through posterolateral approach with posterolateral plate), the option to include the syndesmosis approach in the treatment, and not to include deltoid ligament repair were more noticeable from the combination of CT and radiography, among all groups of expertise, with high inter-observer reliability. Conclusion: The usual radiographs may fail to demonstrate subtle lesions, as posterior malleolus fractures and syndesmotic injuries. The tomographic evaluation increases the precision of diagnosis and improves the quality of information that the surgeon receives, providing data that can positively affect patient care.